Competition between hatchery-reared and naturally-spawned juvenile Chinook salmon - Weber, Edward D., author; Fausch, Kurt D., advisor; White, Gary C., committee member; Myrick, Christopher, committee member; Poff, N. LeRoy, committee member (Colorado State University. Libraries, 2003)
Competition between hatchery-reared and wild salmon has been described as an important negative ecological interaction, but has not been well studied for Chinook salmon Oncorhynchus tshawytscha. I reviewed evidence for competition between hatchery and wild salmonids in streams, tested the effects of adding hatchery-reared juvenile Chinook salmon on emigration, growth, and survival of their wild counterparts, and measured the abundance of juvenile Chinook salmon in two rearing areas downstream of a hatchery in the Sacramento River, California before and after hatchery releases. Most published studies indicated that adding hatchery salmonids had negative effects on wild salmonids in streams. However, few direct studies of competition have been conducted, and most were designed to quantify the effects of specific stocking programs rather than the relative competitive ability of the two types. In three years of displacement experiments, emigration rates of wild salmon from 8-m2 enclosures were similar between controls that contained only wild fish at carrying capacity and treatments to which hatchery fish were also added, indicating that hatchery fish did not force wild fish to emigrate. In two years of competition experiments where fish could not emigrate, I found no evidence that adding hatchery fish affected wild fish survival over two-week periods. However, adding hatchery fish reduced specific growth rates of wild fish during 2002. Furthermore, adding hatchery fish had a greater effect than adding the same density of wild fish, indicating that competitive ability differed between groups. During 2001, I found no evidence that adding hatchery fish reduced wild fish growth rates, probably because the carrying capacity of enclosures was underestimated. Densities of wild juvenile salmon in two rearing locations followed a unimodal trend throughout the spring during 2001 and 2002, and declined by the time hatchery fish were released. Sampling after releases suggested that few hatchery fish used the areas. Of those, most were smaller than the average size of hatchery fish released and probably left the areas within 1-3 d. These data suggest that competitive interactions between the two groups may not be intense in rearing areas of the upper river because salmon densities are low after releases.
Keywords: aquaculture; fish production; ecology; aquatic sciences